Organocatalytic asymmetric cascade reaction of gamma-substituted deconjugated butenolides with o-formyl-beta-nitrostyrene - Deepake, Siddharth K.; Lanjewar, Atul B.; Thatikonda, Thanusha; Gonnade, Rajesh G.; Das, Utpal (ChemistrySelect, 2018)
An efficient chemo-, diastereo- and enantio-selective cascade synthesis of functionalized indanols bearing four contiguous stereogenic centres has been developed via the reaction of beta,gamma-butenolides with o-formyl-beta-nitrostyrenes in the presence of bi-functional hydrogen-bonding catalyst. Indanol derivatives containing gamma,gamma-disubstituted butenolides were obtained in good yields and with moderate to high enantioselectivities/diastereoselectivities.
Keywords: butenolides; Cascade reaction; Enantioselectivity; Indanol; organocatalysis

Alpha-Angelica lactone in a new role: facile access to N-Aryl tetrahydroisoquinolinones and isoindolinones via organocatalytic alpha-CH2 oxygenation - Thatikonda, Thanusha; Deepake, Siddharth K.; Das, Utpal (Organic Letters, 2019)
A method for the direct oxidation of various N-aryl tetrahydroisoquinolines and isoindolines to the corresponding lactams using alpha-angelica lactone as a catalyst was developed. The utility of the method was further demonstrated by synthesis of indoprofen and indobufen.

Alpha-Angelica lactone catalyzed oxidation of benzylic sp(3) C-H bonds of isochromans and phthalans - Thatikonda, Thanusha; Deepake, Siddharth K.; Kumar, Pawan; Das, Utpal (Organic & Biomolecular Chemistry, 2020)
A metal-free organocatalytic system has been developed for highly efficient benzylic C-H oxygenations of cyclic ethers using oxygen as an oxidant. This oxidation reaction utilizes alpha-angelica lactone as a low cost/low molecular weight catalyst. The optimized reaction conditions allow the synthesis of valued isocoumarins and phthalides from readily available precursors in good yields. Mechanistic studies indicate that the reaction pathway likely involves a radical process via a peroxide intermediate.

Alpha-angelica lactone catalyzed oxidation of pyrrolidines to lactams - Deepake, Siddharth K.; Kumar, Manish; Kumar, Pawan; Das, Utpal (European Journal of Organic Chemistry, 2022)
Herein, we report an efficient protocol for the synthesis of gamma-lactams from pyrrolidines and oxygen. The strategy follows a two-step process involving an initial generation alpha-amino alkyl radicals from pyrrolidines and oxygen in presence of 4-dimethylaminopyridine (DMAP) followed by trapping of the radical with oxygen species. This protocol demonstrates good functional group acceptance and provides a direct method to access gamma-lactams. The lactam derivatives were obtained in up to 98 % yield.
Keywords: alpha-Amino alkyl radicals; alpha-Angelica lactone; lactams; Oxidation; Pyrrolidines